Fostering Intercultural Inquiry in Subject‐ Area Curriculum Courses - Dunn, William; Kirova, Anna; Cooley, Miriam; Ogilvie, Greg (Canadian Journal of Education/Revue canadienne de l’éducation, 2009)
This study investigates the infusion of intercultural inquiry into subject‐area curricu‐ lum courses in a teacher education program. Drawing from data that include ques‐ tionnaires, student assignments, and interviews, the research focuses on how student teachers responded to critical explorations of diversity within curriculum courses in second language education, early childhood education, and art education. The find‐ ings indicate that most student teachers had limited prior experiences with diversity, leading to anxiety and uncertainty about their preparedness to work in diverse class‐ rooms. Although many were receptive to intercultural inquiry and perceived its value, some resisted efforts to critically challenge social inequality and privilege. Key words: teacher education, diversity, multicultural education, intercultural inquiry Cet article porte sur l’intégration de la recherche interculturelle dans un programme de formation à l’enseignement. Puisant dans des données tirées entre autres de questionnai‐ res, de travaux d’étudiants et d’entrevues, les auteurs cherchent essentiellement à examiner comment des étudiants‐maîtres réagissent aux explorations critiques de la diversité dans des cours en enseignement d’une langue seconde, en éducation préscolaire et en éducation artistique. D’après les résultats obtenus, la plupart des étudiants‐maîtres avaient au départ peu d’expérience de la diversité ; ils se sentaient donc anxieux et peu sûrs d’eux par rap‐ port à la perspective de travailler dans des classes hétérogènes. Si certains voyaient d’un bon œil la recherche interculturelle et étaient conscients de sa valeur, d’autres se mon‐ traient réticents à défier de façon critique des inégalités et des privilèges sociaux. Mots clés : formation à l’enseignement, diversité, éducation multiculturelle, recherche interculturelle